1997
DOI: 10.1021/bi970634r
|View full text |Cite
|
Sign up to set email alerts
|

Fast Events in Protein Folding:  Relaxation Dynamics and Structure of the I Form of Apomyoglobin

Abstract: The fast relaxation dynamics of the acid destabilized I form of apomyoglobin (pH* 3, 0.15 M NaCl; apoMb-I) following a laser-induced temperature-jump have been probed using time-resolved infrared spectroscopy. Only a fast, single exponential phase is observed (bleach centered at v = 1633 cm-1 and transient absorbance at 1666 cm-1) with relaxation times of 38 ns at 30 degrees C and 36 ns at 57 degrees C; no additional slow (microsecond) phase is observed as previously found in the native form of apomyoglobin. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
(60 reference statements)
4
67
1
Order By: Relevance
“…33,34,[46][47][48][49] However, the solubility problem severely hinders the application of the method to forward folding dynamics. We adopted the strategy developed by Wright and co-workers and increased the solubility of apoMb by adding 10% ethanol, 27,40 and were successful in characterizing its entire folding dynamics with a time resolution of 100 μs.…”
Section: Discussionmentioning
confidence: 99%
“…33,34,[46][47][48][49] However, the solubility problem severely hinders the application of the method to forward folding dynamics. We adopted the strategy developed by Wright and co-workers and increased the solubility of apoMb by adding 10% ethanol, 27,40 and were successful in characterizing its entire folding dynamics with a time resolution of 100 μs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, new fast experimental methods Burton et al, 1997;Callendar et al, 1999! have shown that proteins can fold at nearly diffusion-limited rates, on submillisecond time scales~Huang & Oas, 1995; Ballew et al, 1996aBallew et al, , 1996bPascher et al, 1996;Burton et al, 1997;Chan C-K et al, 1997; Gilmanshin et al, 1997aGilmanshin et al, , 1997bGilmanshin et al, , 1998!. Energy landscapes provide the language that can help describe folding events at any level, from the microscopic to the macroscopic.…”
Section: Ensemble Perspectivementioning
confidence: 99%
“…The amide IЈ band of polypeptides is due mainly to the amide CAO stretch vibration. Its sensitivity to conformation and conformational change is well documented (22)(23)(24)(25)(26). Although the protein amide IЈ band has been used extensively for conformation analysis, it is often difficult to differentiate signals arising from different residues because the transitions are broadened from both inhomogeneous and homogeneous mechanisms.…”
mentioning
confidence: 99%